STRUKTUR ANATOMI DAN IDENTIFIKASI DELAPAN JENIS KAYU PERDAGANGAN DARI KEBUN PERCOBAAN DI JAWA BARAT - Sri Rulliaty M (Jurnal Penelitian Hasil Hutan, 1988)
Eight  wood  species from  forest  experimental   garden in West Java were observed  for identification purposes.  All  wood species  could  be  identified one  from  the  others,  due  to  their  distinguished   conspicuous   characters. Kecapi  (Sandoricum kucape   Merr.)  on  the  other  hand,   showed   characters  that  matched   only   the  previous   description   of  the  genus.  Such characters,  were apparently not  sufficed to describe  the species.